1992
DOI: 10.1093/nar/20.18.4717
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the antibiotics clindamycin and lincomycin withEscherichia coli23S ribosomal RNA

Abstract: Interaction of the antibiotics clindamycin and lincomycin with Escherichia coli ribosomes has been compared by chemical footprinting. The protection afforded by both drugs is limited to the peptidyl transferase loop of 23S rRNA. Under conditions of stoichiometric binding at 1 mM drug concentration in vitro, both drugs strongly protect 23S rRNA bases A2058 and A2451 from dimethyl sulphate and G2505 from kethoxal modification; G2061 is also weakly protected from kethoxal. The modification patterns differ in that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 21 publications
9
43
0
2
Order By: Relevance
“…3B, lane 2). Furthermore, the translocation efficiency of A-site antibiotics appears to correlate loosely with their affinity for the ribosome, decreasing from sparsomycin (K d < 1 µM) (Lazaro et al 1987) to chloramphenicol (K d ∼ 2-6 µM) (Contreras and Vazquez 1977) and the lincosamides (K d ∼ 4-6 µM) (Contreras and Vazquez 1977;Douthwaite 1992) to linezolid (K d ∼ 20 µM) (Lin et al 1997) and puromycin (K d ∼ 3-4 mM) (Wohlgemuth et al 2006). Recently, it has been demonstrated that while neither linezolid nor the pseudouridine moiety of sparsomycin, which binds to the A and P sites of large subunit, respectively, can stimulate mRNA translocation by themselves, a linezolid-pseudouridine conjugate can induce translocation in a fraction of ribosomes (Li et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3B, lane 2). Furthermore, the translocation efficiency of A-site antibiotics appears to correlate loosely with their affinity for the ribosome, decreasing from sparsomycin (K d < 1 µM) (Lazaro et al 1987) to chloramphenicol (K d ∼ 2-6 µM) (Contreras and Vazquez 1977) and the lincosamides (K d ∼ 4-6 µM) (Contreras and Vazquez 1977;Douthwaite 1992) to linezolid (K d ∼ 20 µM) (Lin et al 1997) and puromycin (K d ∼ 3-4 mM) (Wohlgemuth et al 2006). Recently, it has been demonstrated that while neither linezolid nor the pseudouridine moiety of sparsomycin, which binds to the A and P sites of large subunit, respectively, can stimulate mRNA translocation by themselves, a linezolid-pseudouridine conjugate can induce translocation in a fraction of ribosomes (Li et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Clindamycin, an antibiotic agent belonging to the Lincosamides family, is another example of a PTC-binding drug (46). In D50S, it connects between the PTC and the ribosome exit tunnel ( Figure 5), thus reducing the level of ribosomal flexibility in this area (17).…”
Section: Figurementioning
confidence: 99%
“…Resistance to lincosamides, macrolides, and chloramphenicol in bacteria and chloroplasts is commonly associated with mutations affecting the peptidyl transferase loop of 23S rRNA (5,7,10,11). Although sequence analysis of T. gondii ribosomal genes suggests that both cytoplasmic and mitochondrial ribosomes are resistant to clindamycin and macrolides, the putative ribosomal genes from the 35-kb element are likely to be sensitive to these drugs (1).…”
Section: Fig 10mentioning
confidence: 99%